A diatom, stomatocyst and pigment calibration dataset for lakes and ponds of the Larsemann Hills, East-Antarctica - Verleyen, E; Vyverman, W; Sabbe, K; Roberts, D; Andrew McMinn; Hodgson, D (2003)
No description available